PENGARUH LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA PEGAWAI PADA KANTOR SEKRETARIAT DAERAH KABUPATEN ACEH UTARA - Zulfikar, Zulfikar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
The influence of the work environment and organizational commitment on employee job satisfaction with self efficacy as a moderating variable at the Regional Secretariat of North Aceh Regency. This study sampled as many as 100 respondents, namely employees at the North Aceh District Secretariat. This research is a quantitative research. Data collection instruments are using a questionnaire. Determination of respondents using nonprobability sampling method. The analysis used in this study is multiple linear regression analysis. The results of this study indicate that the work environment has a positive effect on employee job satisfaction. Hopefully this research will be input for leaders to make policies related to the work environment and organizational commitment to job satisfaction of employees in the organization and hopefully also this research can be used as input or comparison for the organization regarding the influence of the work environment, organizational commitment and self efficacy of employee job satisfaction